3D string theory and Umbral moonshine. (5th September 2017) - Kachru, Shamit; Paquette, Natalie M; Volpato, Roberto
Abstract: The simplest string theory compactifications to 3D with 16 supercharges—the heterotic string on T   7, and type II strings on K 3 × T 3 —are related by U-duality, and share a moduli space of vacua parametrized by O ( 8, 24 ; Z )   \   O ( 8, 24 )   /   ( O ( 8 ) × O ( 24 ) ) . One can think of this as the moduli space of even, self-dual 32-dimensional lattices with signature (8, 24). At 24 special points in moduli space, the lattice splits as Γ 8, 0 ⊕ Γ 0, 24 . Γ 0, 24 can be the Leech lattice or any of 23 Niemeier lattices, while Γ 8, 0 is the E 8 root lattice. We show that starting from this observation, one can find a precise connection between the Umbral groups and type IIA string theory on K 3. This may provide a natural physical starting point for understanding Mathieu and Umbral moonshine. The maximal unbroken subgroups of Umbral groups in 6D (or any other limit) are those obtained by starting at the associated Niemeier point and moving in moduli space while preserving the largest possible subgroup of the Umbral group. To illustrate the action of these symmetries on BPS states, we discuss the computation of certain protected four-derivative terms in the effective field theory, and recover facts about the spectrum and symmetry representations of 1/2-BPS states.